KEPUASAN PELANGGAN DAN PRICE ACCEPTANCE : STUDI PADA PENUMPANG PENERBANGAN NASIONAL - Farida Jasfar (Universitas Trisakti, 2003)
This research focused on customer satisfaction and price acceptance where participated by 457 respondents of domestic air fight passengers. By using causality research method, where customer satisfaction was measured by 5 scale attitudes and price acceptance was measured by customer readiness to pay based on services perceived. The result of this research demonstrated that overall customersatisfaction toward price accep- tance 37.5% is influenced. Others excluded variables in the research model have influenced for 62.5%. Each classification of customer satisfaction come up with two differentresult. The austomer satisfaction which falls into middie range is insignificant toward prince acceptance, different form the one that fals into lower range and higher range which influenced significantly. The mean of low customer satisfaction that it will significantly contribute toward decreasing price acceptance.